Effect of tropical precipitation on C-band spread spectrum VSAT - Teo, David Choon Huat. (2008)
This report presents the findings of the study done on the effect of rain attenuation on C-band spread spectrum VSAT (Very Small Aperture Terminal) system. The C-band spread spectrum VSAT system is implemented using a pair of SIGTEK spread spectrum ST-112 transmitter and ST-108 receiver cards together with an Agilis AAV880 integrated single package RF transceiver and a Channel Master 2.4 metres offset parabolic antenna. The RG50 tipping bucket rain gauge and RDS1 data logger from Seba Hydrometrie are used to collect and record the instantaneous rainfall throughout the period of study.